Exploring expert opinion on the practicality and effectiveness of biosecurity measures on dairy farms in the United Kingdom using choice modeling - Shortall, Orla; Green, Martin; Brennan, Marnie L.; Wapenaar, Wendela; Kaler, Jasmeet (American Dairy Science Association, 2017)
Biosecurity, defined as a series of measures aiming to stop disease-causing agents entering or leaving an area where farm animals are present, is very important for the continuing economic viability of the United Kingdom dairy sector, and for animal welfare. This study gathered expert opinion from farmers, veterinarians, consultants, academics, and government and industry representatives on the practicality and effectiveness of different biosecurity measures on dairy farms. The study used best-worst scaling, a technique that allows for greater discrimination between choices and avoids the variability in interpretation associated with other methods, such as Likert scales and ranking methods. Keeping a closed herd was rated as the most effective measure overall, and maintaining regular contact with the veterinarian was the most practical measure. Measures relating to knowledge, planning, and veterinary involvement; buying-in practices; and quarantine and treatment scored highly for effectiveness overall. Measures relating to visitors, equipment, pest control, and hygiene scored much lower for effectiveness. Overall, measures relating to direct animal-to-animal contact scored much higher for effectiveness than measures relating to indirect disease transmission. Some of the most effective measures were also rated as the least practical, such as keeping a closed herd and avoiding nose-to-nose contact between contiguous animals, suggesting that real barriers exist for farmers when implementing biosecurity measures on dairy farms. We observed heterogeneity in expert opinion on biosecurity measures; for example, veterinarians rated the effectiveness of consulting the veterinarian on biosecurity significantly more highly than dairy farmers, suggesting a greater need for veterinarians to promote their services on-farm. Still, both groups rated it as a practical measure, suggesting that the farmer-veterinarian relationship holds some advantages for the promotion of biosecurity.